Biogas production from modification of food waste anaerobic digestion process - Fathia Khairunnisa Chantika; Warmadewanthi IDAA; Vu Bich Hanh Dang (BIO Web of Conferences)
Food waste is Indonesia’s largest solid waste composition, and most of it is disposed of directly into landfills. Food waste is a suitable substrate for anaerobic digestion. This study was conducted to examine the effect of adding mixed cultures of methanogen bacteria (MCB) on food waste anaerobic digestion. Variables used in this study were the percentage of MCB added and its addition frequency. The quantity of MCB added is calculated based on the percentage of MCB to the solid waste weight, which is 10%, 30%, and 50%. The frequency of MCB added is every 10 and 15 days. The addition was carried out starting on day 0. Results of this study showed that the variation of 50% MCB added every 15 days had the highest biogas cumulative production, up to 201.5 liters. The result showed that the anaerobic process was under mesophilic conditions, varying from 28-30°C. Moisture content was increased with the addition of MCB. Temperature, pH, moisture content, and C/N ratio testing were also examined at the end of the study to determine the result product quality. It was shown that moisture content and C/N value were still high, which explains that the anaerobic degradation has not been done yet.